Practices for Research Integrity Promotion in Research Performing Organisations and Research Funding Organisations: A Scoping Review - Ščepanović, Rea (Sci Eng Ethics, 2021)
Research integrity (RI) is a continuously developing concept, and increasing emphasis is put on creating RI promotion practices. This study aimed to map the existing RI guidance documents at research performing organisations (RPOs) and research funding organisations (RFOs). A search of bibliographic databases and grey literature sources was performed, and retrieved documents were screened for eligibility. The search of bibliographical databases and reference lists of selected articles identified a total of 92 documents while the search of grey literature sources identified 118 documents for analysis. The retrieved documents were analysed based on their geographical origin, research field and organisational origin (RPO or RFO) of RI practices, types of guidance presented in them, and target groups to which RI practices are directed. Most of the identified practices were developed for research in general, and are applicable to all research fields (n = 117) and medical sciences (n = 78). They were mostly written in the form of guidelines (n = 136) and targeted researchers (n = 167). A comprehensive search of the existing RI promotion practices showed that initiatives mostly come from RPOs while only a few RI practices originate from RFOs. This study showed that more RI guidance documents are needed for natural sciences, social sciences, and humanities since only a small number of documents was developed specifically for these research fields. The explored documents and the gaps in knowledge identified in this study can be used for further development of RI promotion practices in RPOs and RFOs. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s11948-021-00281-1.